Chemical composition and antibacterial activity of the essential oil from aerial parts of Porophyllum ruderale (Jacq.) Cass. collected in Venezuela - Rondón, María; Delgado, Jonathan; Velasco, Judith; Rojas, Janne; Rojas, Luis; Morales, Antonio; Carmona, Juan (Ciencia)
Essential oil from the fresh aerial parts of Porophyllum ruderale (Jacq.) Cass. (Asteraceae) collected in January 2005 was analyzed by GC/MS. The oil was obtained by hydrodistillation with a 0.18% w/v extraction yield. Twenty three components were identified by comparison of their mass spectra with the mass spectra of a GC- MS Library data and the retention indices calculated for every compound. The main constituents were a mixture of limonene and b-phellandrene (50.3%), sabinene (20.2%), 1- undecene (4.7%), 4- terpineol (3.8%) and a-pinene (2.9 %). Antibacterial activity of the essential oil of this species was evaluated against Gram positive (Staphylococcus aureus, Enterococcus faecalis) and Gram negative (Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa) bacteria using the disc diffusion agar method. The results showed a broad spectrum of activity with minimal inhibitory concentration (MIC) values ranging from 20 to 200 μg/mL.